Work schedule system application at PT. Asima Jaya Teknik Bekasi - Acmad Nurhadi; Elly Indrayuni (Journal of Information System, Informatics and Computing, 2022)
With the Covid-19 virus still making us have to innovate in the field of technology to support a job. and to find out the problems that exist in PT. Asima Jaya Teknik, the method used is the waterfall method, where the Waterfall Model is divided into four stages, requirements analysis, design, coding, and testing. PT. Asima Jaya Teknik, in the process of recap work it is still not computerized so that in carrying out the process, errors are still encountered starting from when inputting data to getting work to billing data. The process is still manual using paper, so there is often loss and damage, sometimes between one employee and another having data that is not the same, so they have to work twice to correct data from other employees. The results of this study create an application that is used to recap the work of employees that can help and alleviate and speed up the work process at PT. Asima Jaya Engineering. In addition, it can also save time and energy from the employees of PT. Asima Jaya Engineering.